Surface plasmon resonance sensor composed of microstructured optical fibers for monitoring of external and internal environments in biological and environmental sensing - Liu, Wei; Liu, Chao; Wang, Jianxin; Lv, Jingwei; Lv, Yan; Yang, Lin; An, Ni; Yi, Zao; Liu, Qiang; Hu, Chunjie; Chu, Paul K. (Results in physics, 2023)
•This novel sensor can simultaneously detect gas–liquid analytes in the external and internal environment of organisms.•The proposed MOF-SPR sensor can be operated in the infrared range to detect the analyte RIs of ultra-wide scope from 1.00 to 1.38.•Maximum wavelength sensitivity is 20,000 nm/RIU boasting a resolution of 5.00 × 10−6 RIU.•Compared to the single-open-loop model, this dual-open-loop design is capable of bidirectional and simultaneous excitation of SPR to further promote sensing properties. To achieve simultaneous detection of analytes with different states in internal and external environments, A microstructured optical fibers (MOFs) biochemical sensor based on surface plasmon resonance (SPR) is proposed. The micro-polished dual-open-loop structure with anti-corrosive gold as the sensing layer is designed, which greatly improves the phase matching between fundamental mode and plasmonic mode to further stimulate SPR effect. Numerical simulation by the full-vector finite element method (FEM) reveals that the even mode for y-polarized state has better sensing properties due to the more eminent electric field distribution and shift of the confinement loss peak. In order to better evaluate and analyze the output characteristics of this sensor, the wavelength modulation and amplitude interrogation methods are adopted. The results manifest that the maximum wavelength sensitivity (WS) of 20,000 nm/RIU and amplitude sensitivity (AS) of 208.21 RIU−1 with resolution (R) of 10−6 order can be acquired in operable infrared region (900–2,750 nm). Furthermore, this sensor has realized a broad range of detection for gas and liquid analytes with RIs from 1.00 to 1.38. On account of its simple structure, low cost, and industrial compatibility, this sensor has large potential in environmental and biological applications such as atmospheric monitoring, sewage treatment, food safety, humoral regulation, and medical diagnosis.